2017
DOI: 10.1038/srep45187
|View full text |Cite
|
Sign up to set email alerts
|

Brain arousal regulation as response predictor for antidepressant therapy in major depression

Abstract: A tonically high level of brain arousal and its hyperstable regulation is supposed to be a pathogenic factor in major depression. Preclinical studies indicate that most antidepressants may counteract this dysregulation. Therefore, it was hypothesized that responders to antidepressants show a) a high level of EEG-vigilance (an indicator of brain arousal) and b) a more stable EEG-vigilance regulation than non-responders. In 65 unmedicated depressed patients 15-min resting-state EEGs were recorded off medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 51 publications
4
40
0
Order By: Relevance
“…According to the Arousal Regulation Model of Affective Disorders [7,8], hypostable and hyperstable levels of arousal contribute to manic and depressive-like behavior, respectively. Several empirical studies have supported this model [9][10][11][12]. Notably, similar concepts have previously been proposed on the relationship between arousal and the personality traits extraversion [13] and sensation seeking [14].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…According to the Arousal Regulation Model of Affective Disorders [7,8], hypostable and hyperstable levels of arousal contribute to manic and depressive-like behavior, respectively. Several empirical studies have supported this model [9][10][11][12]. Notably, similar concepts have previously been proposed on the relationship between arousal and the personality traits extraversion [13] and sensation seeking [14].…”
Section: Introductionsupporting
confidence: 71%
“…Indeed, depressive patients often experience insomnia, show delayed sleep onset, and benefit from sleep deprivation [48][49][50]. In addition, several studies have provided direct evidence for enhanced levels of brain arousal in depression [9][10][11][12]. Moreover, we observed that increased imputed expression levels of TMEM159 correlated with persistently high arousal levels, and the MetaXcan database suggests, by analogy, increased TMEM159 expression levels in independent cohorts of patients with Major Depression, Autism Spectrum Disorder, and Alzheimer's Disease [45].…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional arousal responses are a core component of many neuropsychiatric disorders. For example, patients with anxiety disorders often show hyperarousal responses to negatively salient stimuli, and patients suffering from depression show hypoarousal responses to positively salient stimuli (Craske et al, 2009;Lang and McTeague, 2009;Patriquin et al, 2019;Schmidt et al, 2017;Urbano et al, 2017;Wilhelm and Roth, 2001). Elucidating the neural circuit elements that orchestrate changes in physiological arousal are thus essential for understanding maladaptive motivational states (Marton and Sohal, 2016;Sparta et al, 2013;Touriño et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in dysregulation of arousal as a transdiagnostic process (Hegerl and Hensch, 2014;Huang et al, 2015;Sander et al, 2015) contributing not only to the pathogenesis of depression (Hegerl et al, 2012) but also to other psychiatric disorders including anxiety (Domschke et al, 2010) and chronic pain disorders (Foo and Mason, 2003); indeed arousal has become a transdiagnostic research domain in the Research Domain Criteria project (RDoc) (Cuthbert, 2014;Morris and Cuthbert, 2012). Furthermore, increased arousal in depression (Hegerl et al, 2012;Schmidt et al, 2016Schmidt et al, , 2017 may be an important determinant of antidepressant treatment outcome, with studies showing that a subgroup of responders have heightened and faster reduction of arousal during antidepressant treatment compared to non-responders (Olbrich et al, 2016;Schmidt et al, 2017). Our findings suggest there could be a serotonergic basis to transdiagnostic dysfunctional arousal in psychiatric disorders.…”
Section: Acutely Increased Serotonergic Neurotransmission and Heightementioning
confidence: 57%